Risk Assessment Of Gonggang Dam In Magetan District, East Java Province - Trifad Mochammad Khaidir; Sri Sangkawati; Sriyana Sriyana (Eduvest - Journal of Universal Studies, 2024)
This study aims to assess the safety risk of the Gonggang Dam located in Magetan Regency, East Java, using traditional methods and the event tree method (Event Tree Analysis). The risk assessment is conducted by identifying potential hazards and failure modes, estimating the probability of failure, and evaluating the level of risk based on the analysis results. The results of the analysis show that the event tree method provides acceptable risk results, while the traditional method shows unacceptable risks. The priority of risk management at Gonggang Dam is focused on monitoring the dam body and inundation area to maintain safety and maximize the life of the dam. Recommendations were given to improve structural safety and regular monitoring.